2008
DOI: 10.1007/s10689-008-9216-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of BRCA1/BRCA2 genes’ contribution to breast cancer susceptibility in high risk Jewish Ashkenazi women

Abstract: Major gene rearrangements involving BRCA1 BRCA2 contribute little to the burden of inherited predisposition of breast cancer in Ashkenazi Jews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The existence of large genomic rearrangement was not excluded. However, at least among Ashkenazim, the contribution of such genomic events to the overall burden of inherited predisposition to breast cancer is limited [11,35]. Moreover, the representation of the non Jewish populations may have been suboptimal, as these represent families from three medical centers, which may under represent some sects in the non Jewish populations in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of large genomic rearrangement was not excluded. However, at least among Ashkenazim, the contribution of such genomic events to the overall burden of inherited predisposition to breast cancer is limited [11,35]. Moreover, the representation of the non Jewish populations may have been suboptimal, as these represent families from three medical centers, which may under represent some sects in the non Jewish populations in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…Our report is the first to assess for the presence of large deletions and rearrangements exclusively using the commercially available technology currently in use in the United States (Myriad Genetic Laboratories, Salt Lake City, UT), as opposed to the research technologies employed by the previous investigators. With the addition of this study, a total of 311 AJ probands from high-risk families have now been reported as testing negative for genomic rearrangements using currently available technological methods [17,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may contribute to this incongruity, including genetic drift, overestimation of mutation risk by existing models, mutations in as yet undiscovered cancer susceptibility genes, or the presence of structural alterations, such as large deletions or insertions within the BRCA genes not detected by PCR-based sequence analysis. In three studies reported to date, no major genomic rearrangements were identified among approximately 200 Ashkenazi breast or ovarian cancer patients [17,24,25] using cDNA analysis [24] or Multiplex Ligation-dependent Probe Amplification (MLPA) [17,24,25]. In one study, a significant number of genomic rearrangements were initially identified by MLPA; however, none were confirmed by quantitative polymerase chain reaction (PCR) [25].…”
Section: Introductionmentioning
confidence: 99%
“…The frame shift mutation 10323delCins11 occurring in exon 27 also should be regarded as belonging to changes of indefinite biological effect (according to BIC). The group of detected mutations is completed with nine intron changes in exons 8,11,12,14,15,17,22 and a G203A change in the non-encoding 5 0 UTR segment of exon 2.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 5467insT, 6174delT and 6192delAT mutations exert a particular effect on double DNA strand repair function and strongly predispose to breast cancer development. The 6174delT mutation included in the BIC [13] database is the change occurring most frequently in the population of Ashkenazi Jews, both women and men with breast cancer Codick et al [14] and also Distelman-Menachem et al [15].…”
Section: Discussionmentioning
confidence: 99%